Analisis Ekonomi dan Produksi Usaha Peternakan Ayam Broiler Menggunakan Tipe Kandang Closed House Dua Lantai Dan Tiga Lantai di Kabupaten Kebumen - Rhetno Sugito; Novie Andri Setianto; Yusmi Nur Wakhidati (Fakultas Peternakan Universitas Jenderal Soedirman, 2021)
Background. Broiler chicken business potential has a great opportunity to be used as a livestock business because of the demand from the public to meet their protein needs. Thu, farmer's income is optimal. Technological development is the use of closed house cages. This study aims to calculate the income, calculate BEP, analyze production levels and determine differences in income levels, BEP, and livestock production in broiler chicken farming using two-story closed house and three-story closed house cages. Materials and methods. This research was conducted using a survey method in Kebumen district. Economic analysis and production were carried out by different tests using Student's t-test. Results. The average income in a two-story closed house cage is IDR32,983,219.00/period or IDR1,375.00/livebird and the average income in a three-story closed house cage is IDR43,826,365.00/period or IDR1,908.00/livebird. The average BEP livebird in a two-story closed house is 32,640 and a BEP is priced at IDR17,201.00/kilogram. The average BEP livebird in a three-story closed house is 32,958 and the BEP price is IDR16,849.00. The average production index in the two-story closed house is 367,877 and the production index in the three-story closed house is 392,576. Conclusion. The results showed that there was no difference in income, BEP, and production in two-story closed house and three-story closed house